Presence of Shiga toxin 2e‐producing Escherichia coli and atypical enteropathogenic E. coli in an asymptomatic child. Issue 4 (December 2014) - Fernandes, Miriam Rodriguez; Ignacio, Aline; Martins, Fernando H.; Rocha, Leticia B.; Piazza, Roxane M. F.; Vaz, Tânia M. I.; Avila‐Campos, Mario Julio; Nakano, Viviane
Abstract : Introduction: Escherichia coli causes gastroenteritis in humans and animals. Case presentation: In this study, both Shiga toxin‐producing E. coli (STEC) and atypical enteropathogenic E. coli (EPEC) strains were identified in a stool sample from a healthy child, and they were serotyped as Shiga toxin‐producing E. coli (STEC) ONT : H19 and atypical enteropathogenic E. coli (EPEC) O37 : H45. Conclusion: This is the first report, to our knowledge, of a concomitant presence of diarrhoeagenic E. coli (DEC) strains in an asymptomatic child. None of the microorganisms was able to produce diarrhoea, maybe because they were transient bacteria or because of the good immune status of the child. Attention should be paid to this result and it could be of interest in vaccine prospects.